Suspension-Feeding Benthic Species’ Physiological and Microbiome Response to Salmon Farming and Associated Environmental Changes - Laroche, Olivier; Meier, Sonnich; Mjøs, Svein A.; Keeley, Nigel (Frontiers in Marine Science, 2022)
Caged salmon farming is increasingly undertaken in water bodies with strong hydrodynamics where hard and mixed substrate habitats are more prevalent. Yet, these structurally complex and heterogeneous habitats support diverse benthic communities including several cnidarians and sponges that remain poorly characterized. This study used a combination of respirometry measurements, gas chromatography and 16S rRNA metabarcoding to define the respiration rate, stable carbon (δ13C) and nitrogen isotopes (δ15N), fatty acid (FA) and microbial profiles, and assess the impact of salmon farming on four important epibenthic suspension-feeders along the western Norwegian coast: the sponges Craniella and Weberella, the soft coral Duva florida and the anemone Hormathia digitata. Our results showed striking differences in fatty acid profiles and host microbiome communities in terms of identity, functional capabilities and genetic properties across the suspension-feeders. We found evidence of increased mortality rate in specimens located near fish farm activities and of a species-specific effect on respiration rate, with D. florida showing increased activity under the farm. Effects of fish farming on the suspension feeders were also species-specific and particularly evidenced by functional microbial turnover and by alteration of overall FA profiles in the soft coral and sea anemone. In particular, D. florida showed reduced level of FAs close to the farm (0-350 m), with significant difference in composition along a distance gradient. Only H. digitata showed evidence of incorporation of organic material from the fish farm waste via fatty acids trophic markers (FATM) and stable isotope analysis. Overall, our study demonstrates that suspension feeders have taxon-specific sensitivity towards the effect of salmon farming, and identified several potential molecular indicators that could be used as surrogate of impact gradient upon further research and validation. It also provides a wealth of ecological and physiological information on some of the most common sessile epibenthic organisms within Arctic and sub-Arctic regions, enabling us to better understand their response and evaluate their resilience to environmental changes.